1990
DOI: 10.1021/ja00160a054
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure nucleation in peptides. Transition metal ion stabilized .alpha.-helices

Abstract: 1989, 17. (d) Felix, A. M.; Heimer, E. P.; Wang, C.-T.; Lambros, T.-J.; Fournier, A.; Mowles, T. F.; Maines, S.; Campbell, R. M.; Wegrzynshi, B. B.; Toome, V.; Fry, D.; Madison, V. Int.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
195
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(204 citation statements)
references
References 1 publication
6
195
0
3
Order By: Relevance
“…Stabilizing interactions involving side chains almost always occur between i,i+4 residues, as discussed in chapter 1.2 and evidenced by other results (Ghardiri & Choi, 1990). Based upon NMR spectroscopy (discussed below) the conformations at 0°C and 25°C are identical for the first 17 residues; therefore, the stabilizing interaction occurs beyond residue 17.…”
supporting
confidence: 57%
“…Stabilizing interactions involving side chains almost always occur between i,i+4 residues, as discussed in chapter 1.2 and evidenced by other results (Ghardiri & Choi, 1990). Based upon NMR spectroscopy (discussed below) the conformations at 0°C and 25°C are identical for the first 17 residues; therefore, the stabilizing interaction occurs beyond residue 17.…”
supporting
confidence: 57%
“…1A) (7,8). Such i, i þ 4 diHis motifs have been used for the assembly and stabilization of metalloproteins and peptides through coordination of divalent transition metal ions (9)(10)(11)(12). We have previously shown that MBPC-1 self-assembles into discrete oligomeric structures upon metal coordination by the diHis motifs.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of previous studies regarding natural or engineered metal-binding sites, we rationalized that mutations of solvent-exposed residue pairs i and i þ 4 of a helix [50][51][52][53] or i and i þ 3 of a helixloop 37 to a pair of either histidine or cysteine residues would induce homooligomeric assemblies upon incubation with metal. Specifically, we predicted the metal site within these assemblies to take on a tetrahedral or octahedral coordination, in which the mutated histidines or cysteines among the molecules participate in the metal coordination.…”
Section: Rationale and Design Of Mutationsmentioning
confidence: 99%